TOWARDS THE SUSTAINABLE URBAN DEVELOPMENT OF THE LIMA CALLAO MEGALOPOLIS, PERU, TO 2050 - Castillo-García, Rodolfo Francisco (2020)
This article is the product of academic research, personal reflections, professional experiences, and technical proposals of the author about the urban evolution of the city of Lima (Peru) in the period 1535 - 2020, the evolution of the urban planning of Lima Callao in the period 1949 - 2020, and about the sustainable urban development of the Lima Callao Megalopolis, Peru, with a view to the year 2050. In that perspective, the objective of this article is to make some reflections on the urban evolution of the city of Lima, from the "Colonial Lima" to the "Megalopolis Lima" in the period 1535 - 2020, and of the evolution of the urban planning of Lima Callao, in the period 1949 - 2020. Likewise, technical proposals were submitted to promote the planning of sustainable urban development of the Lima Callao Megalopolis, with a view to the Bicentennial of the Independence of Peru (2021), the 500th anniversary of the Spanish foundation of Lima (2035), and the second half of the 21st Century (2050); within the framework of the 2030 Agenda for Sustainable Development, the New Urban Agenda, and the National Reconstruction Plan with Changes. Keywords: Lima-Callao – megalopolis – sustainable urban development – urban planning